Integrating Acupuncture into a Dialysis Center - Correia de Carvalho, Marta (2023)
A growing interest in integrating traditional Chinese medicine (TCM) and conventional medicine (CM) to create a more comprehensive approach to healthcare has been verified. Scientific evidence supports acupuncture as an integrative treatment for specific health conditions. The aim of this study was to assess the acceptance and feasibility by patients and healthcare professionals of integrating acupuncture in a dialysis center. Individuals undergoing hemodialysis (HD) who participated in a patient-assessor-blinded randomized controlled trial that evaluated the effect of acupuncture on functional capacity and quality of life were included. Acceptance was measured by adherence (percentage of patients who completed treatments and dropouts) and patients' and healthcare professionals' opinions toward acupuncture (pre- and pro-intervention questionnaires). Feasibility was measured by safety (number of reported adverse events) and effectiveness (changes in functional capacity, peripheral muscle strength, and health-related quality of life scores after treatment). Forty-eight patients were included, and forty-five (93.8%) were analyzed. No adverse events were reported. All patients completed the treatment, and only three patients (6.2%) were lost to the 12-week post-treatment follow-up. The attitudes of patients and health professionals were favorable to acupuncture, namely in relation to its use, degree of discomfort, recommendation to others, and interference with routine care and clinical setting. Integrating acupuncture into a dialysis center seems viable and well-accepted by patients with kidney failure on maintenance HD, doctors and nurses.